Analysis of Early Reading Skills of Lower Grade Elementary School Students in Kahayan Tengah Subdistrict, Pulang Pisau Regency - Alifiah Nurachmana; Petrus Poerwadi; Patrisia Cuesdeyeni; Albertus Purwaka; Paul Diman; Afif Restu Fauzi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: The low level of literacy and numeracy among primary school students in Indonesia highlights the need for contextual and engaging learning media that reflect local culture. Conventional teaching methods often fail to capture students’ interest and do not integrate local wisdom effectively. Aim: This research aims to develop and test an interactive animation-based learning media using Central Kalimantan folktales to enhance students’ literacy and numeracy skills in primary education. Method: The study employed a research and development (R&D) approach by designing, validating, and testing a digital prototype that combines animation, narration, and interactivity. Expert validation was conducted to refine the prototype, followed by pilot testing in selected partner schools in Central Kalimantan. Data were collected through observations, questionnaires, and learning assessments, and an alyzed descriptively to evaluate the media’s effectiveness in improving learning outcomes. Results and Discussion: The results indicated that the interactive animation media successfully increased students’ engagement and motivation, leading to higher literacy and numeracy achievement compared to traditional learning tools. Teachers reported that the integration of local folktales provided meaningful and enjoyable learning experiences while reinforcing students’ cultural identity. The discussion emphasizes the potential of culturally grounded digital media to support the thematic learning approach in the Merdeka Curriculum and contribute to the preservation of local culture. Conclusion: The research concludes that the developed interactive animation learning media based on Central Kalimantan folktales is effective in enhancing primary school students’ literacy and numeracy skills. It also demonstrates significant potential for large-scale implementation, commercialization, and collaboration with the creative industry, reaching Technology Readiness Level 5 as a foundation for sustainable dissemination.